Income Redistribution, Consumer Credit,and Keeping up with the Riches - Mathias Klein; Christopher Krause (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
In this study, the relation between consumer credit and real economic activity during the Great Moderation is studied in a dynamic stochastic general equilibrium model. Our model economy is populated by two different household types. Investors, who hold the economy's capital stock, own the firms and supply credit, and workers, who supply labor and demand credit to finance consumption. Furthermore, workers seek to minimize the difference between investors' and their own consumption level. Qualitatively, an income redistribution from labor to capital leads to consumer credit dynamics that are in line with the data. As a validation exercise, we simulate a three-shock version of the model and find that our theoretical set-up is able to reproduce important business cycle correlations.
Keywords: E21; E32; E44; 330; income redistribution; consumer credit; relative consumption motive; business cycles